Study of the properties of a composite material Fe78Si9B13 / GNP in an epoxy matrix (2024)
This study investigates the properties of a composite material obtained by mixing Fe78Si9B13 metallic powders (at %) with graphene nanoplates (GNP) in an epoxy matrix. Four composite types were created with GNP weight proportions of 0%, 0.5%, 1.0%, and 1.5%. The composites were embedded in transparent epoxy with weight proportions of 10%, 15%, and 20%, and then filled into 7 x 20 mm cylindrical probes. Twelve samples were prepared, and another 12 samples were subjected to a longitudinal magnetic field of 1 kG. All samples were tested with a Universal Testing Machine (Model WDW 10E) up to a maximum force of 20 kN. The experiment recorded deformation (ΔH) vs. charge force. Most samples showed a maximum compression resistance of 390 MPa, except for a few that did not exceed 100 MPa. The magnetically oriented samples showed a greater elastic limit in the range of 200 to 270 MPa. Optical microscopy was used to observe the ordering of the particles after the application of the magnetic field. Scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction were used to characterize the structure of the composite components. A vibrating sample magnetometer (VSM) was used to characterize the magnetic behavior of the metallic powders in the composite.